أهمّ التّحديات المواجِهة للنّظام العربي الإقليمي (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يمرّ النّظام العربي الرّاهن بمرحلة تعجّ بالفوضى والثّورات والتّقسيم المخيف، و يتجاوزُ فيها العربي عروبته و إنسانيّته، ويقف عند حدود السيطرة والهيمنة عليه إرضاءً لذاته في ضوء العديد من التحديات المواجهة له، والمسندة تارة إلى النظام العربي ذاته، وتارة أخرى إلى النظام الدولي. فالنظام العربي جزء من النظام العالمي، وكلاهما في حالة تأثر وتأثير متبادل؛ لذا كان لا بد من الوقوف عند أبرز تلك التحديات المتمثلة بالصراعات والحروب التي شهدتها المنطقة العربية والإرهاب، والتحديات المتمخضة عن الفوضى الدولية والشرق الأوسط الجديد والحرب الباردة، وكذلك الطائفية، والتحدي الديمقراطي، إضافة إلى التحدي الخطر المتعلق بالعولمة. Arab system isgoing through today stage chaotic frightening, though and division in which the arab exceed Arabism and humanity and stand at the borders of control and dominance to satisfy it self in light the many challenges faced him, and assigned sometimes to the same arab system and at other times to the international syatem . the arab system is part of the global system and in the case of both affected and mutual effect . so it was necessary to stand at the most prominent of these challenges of conflicts and wars in the arab regiane and terroeism and the challenges wich follow on international chaos and the new middle east , the economic challenges as well as sectarian and the challenge of imported arab democracies as well as the most dangerous challenge on globalization .